2020
DOI: 10.3847/1538-4357/ab698c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Limiting the Depth of Zonal Winds in the Gas Giant Planets

Abstract: Gravity signatures observed by the Juno and Cassini missions that are associated with the strong zonal winds in Jupiter’s and Saturn’s outer envelopes suggest that these flows extend for several thousand kilometers into the interior. It has been noted that the winds seem to abate at a depth where electrical conductivity becomes significant, suggesting that electromagnetic effects play a key role for confining the winds to the outer weakly conducting region. Here, we explore the possible mechanisms for braking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(87 citation statements)
references
References 48 publications
11
76
0
Order By: Relevance
“…A superadiabatic temperature profile may result from stable stratification. Christensen et al (2020) showed that meridional flows in a stably stratified, slightly conducting region slow down the strong zonal flows and suggested the existence of such a region in Jupiter as an explanation for the truncation of the zonal flows, which, according to recent combined analysis of magnetic field and gravity field data, occurs rather sharply at 0.97 R Jup ).…”
Section: H/he Adiabat Modificationmentioning
confidence: 97%
“…A superadiabatic temperature profile may result from stable stratification. Christensen et al (2020) showed that meridional flows in a stably stratified, slightly conducting region slow down the strong zonal flows and suggested the existence of such a region in Jupiter as an explanation for the truncation of the zonal flows, which, according to recent combined analysis of magnetic field and gravity field data, occurs rather sharply at 0.97 R Jup ).…”
Section: H/he Adiabat Modificationmentioning
confidence: 97%
“…Secondly, although different density and temperature profiles are employed in this study, we assume that the whole simulation domain is convectively unstable. Stably stratified layers may exist within giant planets; if so, they could change the magnetohydrodynamics significantly (Stevenson, 1982b; Cao and Stevenson, 2017; Christensen et al, 2020). Finally, our numerical simulations are limited to a small range of control parameters with moderate Ekman numbers.…”
Section: Discussionmentioning
confidence: 99%
“…However, the generation of geostrophic motions is a long-standing issue in the theory of rotating fluids even in the incompressible regime [74]. The observed zonal winds at Jupiter's surface could be also related to deep geostrophic flows [75,76], but different physical scenarios are highly disputed in light of recent high-precision data [77][78][79]. To assess the robustness of the deep scenario, the polynomial formulation might be used directly to solve dynamical problem (5.1) without any prior computations of the normal modes (as for incompressible theories [80,81]).…”
Section: Planetary Implicationsmentioning
confidence: 99%